Effect of the geometric shapes of repair patches on bonding strength. Issue 3 (17th February 2021) - Lee, Hyunhee; Seon, Seokwoon; Park, Soyoun; Walallawita, Rashiga; Lee, Kwangju
ABSTRACT: The effect of repair patches with different geometric shapes on bonding strength was investigated. Four shapes of patches were considered: rectangular patch (RP), triangular patch (TP), inverted triangular patch (IP), and parallelogram patch (PP). The offset distance of two adjacent layers in a repair patch is defined as the tread depth. Four-point bending tests were performed to measure bonding strengths. The bonding strength of IP was the largest because of the spaces between the top and middle layers of patch and the parent structure through which resin easily flowed during repair. There was an optimum tread depth where bonding strength was the largest. Finite element analysis was performed to find the bonding strengths and the positions of crack initiation. The bonding strengths in the analysis had similar trends as in the test results. In RP, the stress was the largest at the end of the fillet, where crack initiation started. In other patches, the stress was the largest in the adhesive near the corner of a glass fiber layer. Amounts of resin that had been impregnated into patches during repair were measured. In IP, resin was impregnated the most uniformly, which enhanced its bonding strength.